Integrating SERVQUAL, Servicescape model and Stimulus-Response Theory to ascertain patronage of specialty coffee outlet - Mohamad Sheriff, Nooraini; Sahak, Siti Zaleha; Ibrahim, Irme Rafhan; Mustafa, Ammar Yasir; Wan Yusoff, Wan Hafiz Aizuddin (Universiti Teknologi MARA, Perlis, 2025)
Customer patronage is critical to the success of a specialty coffee outlet. Based on this, the influence of service quality, physical environment, and promotion on customer’s patronage of a specialty coffee outlet was ascertained in this study. Convenience sampling was used to distribute 350 questionnaires physically at a specialty coffee outlet. The study uncovered that physical environment was the most dominating factor driving customer patronage of the specialty coffee outlet, followed by service quality. To sum, in practice specialty coffee outlets must invest in a welldesigned physical environment to provide an enjoyable and memorable experience for customers that could lead to increase in patronage and business growth. This is possible by leveraging on online influencers producing food review vlogs to showcase their distinctive store ambience and atmosphere of the coffee outlet. Impeccable service quality rendered by specialty coffee outlets too can differentiate a specialty coffee outlet from competitors and attract new customers. Good service quality can elevate customer satisfaction, drive loyalty and ultimately driving patronage. Theoretically, the Stimulus-Response Theory has been extended to integrate the SERVQUAL and Servicescape models together with promotion to ascertain the direct cause of customer’s observable behaviour of patronizing a specialty coffee outlet based on these external stimuli.